A widespread rash with optic neuritis. (7th February 2021) - Lavery, M. J.; O'Brien, B.; Jmor, F.; Price, V.; Guthrie, G.; Khirwadkar, N.; Beare, N.; Wood, M.
Abstract : Click here for the corresponding questions to this CME article.